2010
DOI: 10.1177/1938640010371121
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Doxycycline in Continuous-Instillation Negative Pressure Wound Therapy as "Wound Chemotherapy"

Abstract: Negative-pressure wound therapy (NPWT) is frequently employed in the treatment of complex wounds. The authors present a description of real-time streaming therapy of a variety of wound chemotherapeutic agents through NPWT. Doxycycline, which acts as a competitive inhibitor of matrix metalloproteinases and tumor necrosis factor alpha and further decreases inflammation through the reduction of nitrous oxide production, may prove helpful when delivered in this manner. To the authors' knowledge, this is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Once all tubing was in place, the V.A.C.ULTA™ Therapy System was turned on and set to −125 mmHg, which caused the dressing/drape to collapse within the agar wound model. After a complete seal was achieved and NPWT applied, the peristaltic pump was turned on and set to a rate of 30 cc/hour as previously published (4,5). At the end of 3·5 hours of therapy, the peristaltic pump was turned off and the V.A.C.® Advanced Drape and V.A.C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once all tubing was in place, the V.A.C.ULTA™ Therapy System was turned on and set to −125 mmHg, which caused the dressing/drape to collapse within the agar wound model. After a complete seal was achieved and NPWT applied, the peristaltic pump was turned on and set to a rate of 30 cc/hour as previously published (4,5). At the end of 3·5 hours of therapy, the peristaltic pump was turned off and the V.A.C.® Advanced Drape and V.A.C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, publications have alluded to positive outcomes with the implementation of continuous instillation with the application of NPWT occurring simultaneously (5,6). This method eliminates the typical soak times that are imparted using the traditional NPWTi with periodic‐instillation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…New devices allow infusion and fluid removal with the simultaneous application of local negative pressure [25] . Several kinds of fluids can be applied, mainly antiseptic, topical antibiotic, insulin saline solution [26][27][28] . This system could be useful, especially for contaminated or infected wounds.…”
Section: Wound Chemotherapy With Npwtmentioning
confidence: 99%
“…73 Scimeca et al using NPWTi with insulin in a case report confirmed the efficacy for the treatment of chronic wounds due to emergency amputation at the midfoot level. 34 …”
Section: F Insulinmentioning
confidence: 99%
“…Independently Lessing et al and Scimeca et al demonstrated the effectiveness of continuous instillation even though both used different instilled fluids: saline solution and doxycycline, respectively. 30,34 Argenta and Morykwas presented the benefits resulting from the use of intermittent therapy in standard NPWT, emphasizing the better perfusion of both the wound tissue and surrounding tissues. 3,35 The element of intermittent therapy in NPWTi is unequivocally part of the administered therapy composed of instilled phase with the following dwell time phase, and then with a formation and maintenance of negative pressure.…”
Section: Continuous-versus Periodic-instillationmentioning
confidence: 99%